Ambulantaje en la ciudad de México y la justicia federal - Meneses, Rodrigo (El Colegio de México, 2014)
This paper explores the legal conflicts for the public space in Mexico City. Specifically, it seeks to explain how judges have participated in the legal constitution of specific limits and rules in order to regulate the people’s right to work on the street. The analysis here presented suggests the existence of, at least, three different types of conflicts through which the judicial system has participated in the determination of certain limits, uses and functions of the public space; and, it also, highlights the way in which a particular set of juridical actors have imagined particular ways for regulating the Mexico city’s streets.